On Gender-Sensitive Language - Kuna, Branko; Nujić, Damira (Poznańskie Studia Slawistyczne, 2015)
This paper focuses on changes in Croatian language that either have happened or are possible to happen in order that male dominance in language and gender inequality are reduced. The research concentrates on the use of gender-sensitive language for job titles and occupations of female persons. The study demonstrates the lack of stability in the use of feminine forms, as it has not been integrated into the Croatian language practice yet.